2013
DOI: 10.1016/j.mechmat.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical modeling of the linear viscoelasticity of carbon-black filled styrene butadiene rubbers: The role of the filler–rubber interphase

Abstract: Micromechanics modeling of the linear viscoelasticity of carbon-black filled styrene butadiene rubbers (SBR) shows that a simple representation of a spherical rigid-phase surrounded by rubber gum and embedded in an homogeneous equivalent medium provides access to the effective volume fraction of fillers. This simple representation is successful for a significant range of filler amount, and for materials in the glassy state. For materials in the rubbery state, experimental results support the existence of a fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…Therefore, the latter contain some gum trapped between filler subparticles, and an effective volume content of particles can be defined that we denote f 1 . As explained by Diani et al (2013), the values that are used here are consistent with experimental measures based on the experimental procedure of Medalia (1972). In addition to a volume fraction and an average size, these particles may also have a size distribution, and the distance between nearest neighbors may also be distributed around an average value.…”
Section: Application To a Carbon-black Filled Styrene Butadiene Gumsupporting
confidence: 74%
See 3 more Smart Citations
“…Therefore, the latter contain some gum trapped between filler subparticles, and an effective volume content of particles can be defined that we denote f 1 . As explained by Diani et al (2013), the values that are used here are consistent with experimental measures based on the experimental procedure of Medalia (1972). In addition to a volume fraction and an average size, these particles may also have a size distribution, and the distance between nearest neighbors may also be distributed around an average value.…”
Section: Application To a Carbon-black Filled Styrene Butadiene Gumsupporting
confidence: 74%
“…Then, assuming that the viscoelastic shear modulus of the interphase is enhanced compared to the viscoelastic shear modulus of the bulk gum shown in Fig. 3, because of a reduced molecular mobility, and assuming the carbon black is elastic and incompressible, with G 1 = 70 GPa, Diani et al (2013) experiment is shown in Fig. 4 for the SBR filled with 40 per hundred rubber (phr) carbon black, where a 30% effective volume fraction of filler could be evaluated.…”
Section: Materials and Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, in order to understand how the degradation of the rubber-filler interface may have such a drastic impact on the mechanical response of the filled rubbers, another explanation must be taken into account. Actually, the micromechanics analysis of the linear viscoelasticity of carbon-black filled rubbers is in favor of the existence of a layer at the rubber-filler interface significantly stiffer than the rubber matrix due to restrained mobility [9]. A degradation of this layer, by desorption for instance, may have a significant impact on the material stiffness.…”
Section: Introductionmentioning
confidence: 99%